Consciousness of subjective time in the brain - Nyberg, Lars; Kim, Alice S. N.; Habib, Reza; Levine, Brian; Tulving, Endel (Proceedings of the National Academy of Sciences - PNAS, 2010)
"Mental time travel" refers to conscious experience of remembering the personal past and imagining the personal future. Little is known about its neural correlates. Here, using functional magnetic resonance imaging, we explored the hypothesis that mental time travel into "nonpresent" times (past and future) is enabled by a special conscious state (chronesthesia). Well-trained subjects repeatedly imagined taking one and the same short walk in a familiar environment, doing so either in the imagined past, present, or future. In an additional condition, they recollected an instance in which they actually performed the same short walk in the same familiar setting. This design allowed us to measure brain activity correlated with "pure" conscious states of different moments of subjective time. The results showed that the left lateral parietal cortex was differentially activated by nonpresent subjective times compared with the present (past and future > present). A similar pattern was observed in the left frontal cortex, cerebellum, and thalamus. There was no evidence that the hippocampal region is involved in subjective time travel. These findings provide support for theoretical ideas concerning chronesthesia and mental time travel.